Computational fluid dynamic modelling of the Frood-Stobie ice stope thermal storage for mine ventilation heating - Trapani, K.; Chen, Z. (Deep Mining 2017: Proceedings of the Eighth International Conference on Deep and High Stress Mining, 2017)
Deep mines are subject to increased heat loads from the ventilation air, which undergoes auto-compression and increases approximately 1°C per 100 m. Also, mines located in sub-arctic climates require the mine ventilation air to be heated in winter to ensure that icing does not occur within the ventilation shaft. Ice stopes, a system by which ice is created underground by spraying warm return service water onto the cold incoming air in winter, can be utilised for both heating and cooling. The ice storage can be maintained till cooling is required in summer, at which point the ice is melted and the resulting chilled water is similarly sprayed onto the oncoming ventilation air to cool it down, in a bulk air cooler. Computations fluid dynamics simulation, using ANSYS Fluent, was conducted to allow more control on the system and optimise the ice creation within the stope. Simulation results showed higher snow yields and heat transfer efficiencies in colder temperatures with simulations conducted for -5 to -30°C. The maximum air temperature which could be achieved at the stope air outlet, while still resulting in the water particles being fully frozen, was approximately -2.2°C. A linear correlation could be derived between the optimal water flow rate required (for maximum heating and ice fraction of one) and the inlet air temperature, allowing some control on the system’s performance. Future work will concentrate on establishing the best water spray parameters to melt the ice within the stope and produce chilled water to be used in the bulk air cooler.